2022
DOI: 10.1111/bju.15685
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term renal function in patients with chronic kidney disease following radical cystectomy and orthotopic neobladder

Abstract: To evaluate long-term renal function in patients with chronic kidney disease (CKD) Stage IIIa who underwent radical cystectomy and orthotopic neobladder (RC/ONB) compared to matched controls. Patients and MethodsUsing our Institutional Review Board-approved institutional database, patients with a glomerular filtration rate (GFR) of 45-59.9 mL/min/1.73 m 2 who underwent RC/ONB were identified. A control group of patients with a GFR of ≥60 mL/min/1.73 m 2 was selected. Groups were matched based on age, baseline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…A meta-analysis did not show significant difference in serum creatinine between patients with sigmoid and ileal neobladder, and the renal function was well maintained within the normal range in those with normal renal functions prior to surgery [26]. A recent study from our center even demonstrated that patients with chronic kidney disease stage IIIa who undergo neobladder have comparable postoperative renal function to those with a GFR of 60 ml/min [55].…”
Section: Renal Function Deteriorationmentioning
confidence: 82%
“…A meta-analysis did not show significant difference in serum creatinine between patients with sigmoid and ileal neobladder, and the renal function was well maintained within the normal range in those with normal renal functions prior to surgery [26]. A recent study from our center even demonstrated that patients with chronic kidney disease stage IIIa who undergo neobladder have comparable postoperative renal function to those with a GFR of 60 ml/min [55].…”
Section: Renal Function Deteriorationmentioning
confidence: 82%
“…To determine renal function decline, our study referred to previous journals and combined various definitions using different values and ratios [ 13 16 17 18 19 20 21 22 23 24 ]. The follow-up duration and interval were different between previous studies; we followed up the renal function after cystectomy for 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…The follow-up duration and interval were different between previous studies; we followed up the renal function after cystectomy for 5 years. Other studies defined the renal function decline by comparing the assessment and preoperative periods using only one episode [ 13 18 19 22 ]. We questioned this definition and determined that renal function decline should be used when there were two or more consecutive episodes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations